Análise da questão dos refugiados climáticos - Luca, Priscila de (2019)
The present paper aims to develop a study about the problem of people moving about climate issues around the world. Studies carried out by the Internal Displacement Monitoring Center in the year 2014 verified the existence of 19,300,000 forced environmental displaced persons due to floods, storms, earthquakes and tsunamis resulting directly or indirectly from the relation society and nature, such as the increase of the global temperature by reason greenhouse gas emissions, acid rain, river pollution, industrial accidents, nuclear testing, mega-projects for development, depletion of environmental resources and environmental degradation. Although they are forced to move, they do not qualify as refugees as defined in the 1951 Convention Relating to the Status of Refugees, which is why they can not receive the specific aid for that group of persons. This impossibility of framing refugees leads us to instigate a greater debate on the issue (at national and international scales), so that new measures can be created and with this, a better solution to the population displacement resulting from climate change in the world. In this context, the present work has two central points: (i) to verify the emergence of a new category of refugees not protected by the current international instruments and (ii) to analyze the evolution of environmental problems that potentiate climate change. In order to do so, a brief exposition of the refugee concept (under the historical perspective of international law) will be carried out, as well as the current concepts of existing climate refugees, the worsening causes of forced displacement and the global debates on the subject. In order to fill the normative gap, an integrated approach is proposed, developing an effective national, regional and international legal arrangement through the dialogue between the States and International Organizations, so that a true international cooperation exists that seeks to solve the displacements forced by the changes and to establish policies not only for the reception of such refugees after the occurrence of harm (as has been done by the United Nations High Commissioner for Refugees and private institutions) but also for preventive actions to mitigate environmental effects in countries where there is possibility of displacement.